2007
DOI: 10.1111/j.1462-2920.2007.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic ammonium‐oxidizing bacteria in marine environments: widespread occurrence but low diversity

Abstract: Laboratory and field studies have indicated that anaerobic ammonium oxidation (anammox) is an important process in the marine nitrogen cycle. In this study 11 additional anoxic marine sediment and water column samples were studied to substantiate this claim. In a combined approach using the molecular methods, polymerase chain reaction (PCR), qualitative and quantitative fluorescence in situ hybridization (FISH), as well as (15)N stable isotope activity measurements, it was shown that anammox bacteria were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
255
4
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 310 publications
(284 citation statements)
references
References 37 publications
13
255
4
2
Order By: Relevance
“…We were not sure whether some of the unidentified Planctomycetes (2.36 % of total bacteria) were anammox bacteria. Our current results also showed that anammox bacteria were present not only in the freshwater and marine environments (Schmid et al 2007;Wang and Gu 2012;Woebken et al 2008), but also in the complicated landfill system. This expands our knowledge on the biogeography of anammox bacteria.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We were not sure whether some of the unidentified Planctomycetes (2.36 % of total bacteria) were anammox bacteria. Our current results also showed that anammox bacteria were present not only in the freshwater and marine environments (Schmid et al 2007;Wang and Gu 2012;Woebken et al 2008), but also in the complicated landfill system. This expands our knowledge on the biogeography of anammox bacteria.…”
Section: Discussionsupporting
confidence: 75%
“…Candidatus Kuenenia stuttgartiensis is a salt-and alkaline-resistant bacterium Strous et al 2006), and it was detected mostly in wastewater treatment system (Egli et al 2001;Schmid et al 2000). Previous research showed that anammox diversity was usually low in an ecosystem (Schmid et al 2007;Kartal et al 2007). In our bioreactor, anammox bacteria detected by qPCR accounted for 0.27 % of total bacteria, and the value was higher than that from the pyrosequencing method.…”
Section: Discussionmentioning
confidence: 99%
“…Various anoxic marine ecosystems have been monitored for anammox activity and the presence of anammox cells (Kuypers et al 2003Rysgaard et al 2004;Risgaard-Petersen et al 2004;Schmid et al 2007). The anammox bacteria in marine environments seem to be restricted to the Scalindua branch with relatively little biodiversity as reflected in very similar 16S rRNA gene sequences (Fig.…”
Section: The Anammox and Nc10 Bacteriamentioning
confidence: 99%
“…4. In various ecosystems, anammox and NC10 bacteria will be dependent on the activity of aerobic ammonia-oxidizing bacteria under oxygen-limited conditions, e.g., at the oxic/anoxic interface (Dalsgaard et al 2003;Schmid et al 2007;Lam et al , 2009). Oxic/anoxic interfaces are abundant in nature, for example in the rhizosphere of helophytes, biofilms, and marine sediments (Murray et al 1989).…”
Section: Temperaturementioning
confidence: 99%
“…Nutrient profiles, activity measurements, ladderane lipids analysis, 16S rRNA gene sequences and fluorescent in situ hybridization showed that Candidatus 'Scalindua sorokinii' was present and active in the anoxic basin of the Black Sea (Kuypers et al, 2003). In the meantime, many studies have shown that the anammox bacteria and the annamox process are ubiquitous and constitute a substantial sink of fixed nitrogen in the oceans (Dalsgaard et al, 2003;Kuypers et al, 2003;Penton et al, 2006;Schmid et al, 2007). The process is also significant in minimum oxygen zones (Kuypers et al, 2005;Hamersley et al, 2007;Jaeschke et al, 2007), sediments (Engstrom et al, 2005;Penton et al, 2006) and estuaries (Trimmer et al, 2003;Tal et al, 2005).…”
Section: Introductionmentioning
confidence: 99%